2019
DOI: 10.3389/fchem.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Folded Synthetic Peptides and Other Molecules Targeting Outer Membrane Protein Complexes in Gram-Negative Bacteria

Abstract: Conformationally constrained peptidomimetics have been developed to mimic interfacial epitopes and target a wide selection of protein-protein interactions. ß-Hairpin mimetics based on constrained macrocyclic peptides have provided access to excellent structural mimics of ß-hairpin epitopes and found applications as interaction inhibitors in many areas of biology and medicinal chemistry. Recently, ß-hairpin peptidomimetics and naturally occurring ß-hairpin-shaped peptides have also been discovered with potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 89 publications
(114 reference statements)
0
50
0
Order By: Relevance
“…The regulation of porin expression involves several modes of regulation. In addition, the final assembly as functional trimers into the OM is tightly controlled by the BAM machinery but also requires LPS binding 26,[142][143][144] . These complex and partly redundant systems efficiently control the production of porins, which represent a prominent part of the OM protein landscape and are directly involved in OM permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of porin expression involves several modes of regulation. In addition, the final assembly as functional trimers into the OM is tightly controlled by the BAM machinery but also requires LPS binding 26,[142][143][144] . These complex and partly redundant systems efficiently control the production of porins, which represent a prominent part of the OM protein landscape and are directly involved in OM permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro data revealed that besides LptA, thanatin binds to the LptDE complex in the low nanomolar range and, furthermore, its binding site in LptA has been shown by modeling studies to be highly conserved in the periplasmic domain of LptD (Robinson, 2019). This suggests that thanatin can inhibit multiple protein-protein interactions required for the Lpt complex assembly.…”
Section: Discussionmentioning
confidence: 99%
“…This adds to the previously described peculiarities of the P. aeruginosa LptDE translocon, that differs from the E. coli counterpart for the presence of an additional domain of unknown function at the LptD N-terminus 14 , a larger lumen volume 26 , and the specific role of LptE, that is important as LptD chaperone and plug but is not directly involved in LPS transport 22 . The unique features of the P. aeruginosa LptD periplasmic domain have been proposed to justify the anti-pseudomonads specificity of recently identified peptidomimetics targeting LPS transport through interaction with LptD [27][28][29] . Since the cell envelope biogenesis pathways are nowadays considered attractive targets for novel antibacterial drugs [29][30][31] , this emphasizes the potential impact of investigating the conserved and divergent aspects of these systems in different human pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The unique features of the P. aeruginosa LptD periplasmic domain have been proposed to justify the anti-pseudomonads specificity of recently identified peptidomimetics targeting LPS transport through interaction with LptD [27][28][29] . Since the cell envelope biogenesis pathways are nowadays considered attractive targets for novel antibacterial drugs [29][30][31] , this emphasizes the potential impact of investigating the conserved and divergent aspects of these systems in different human pathogens. This information could indeed ultimately drive the rational design of new narrow-or broad-spectrum antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%